A review of the macro-economic policy environment of the OECS: 1980-1995 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
This paper examines the objectives and instruments of macroeconomic policy and highlights important developments and policy changes over the period 1980-1995 in policy formulation and implementation for the five member countries of the OECS sub-region. While the interdependence of macroeconomic policies is recognised, the policies are analysed separately for simplicity. The data presented in this report were obtained from a number of sources both international and local. There were serious discrepancies is the data in some instances and complete lack of data in others. The analysis should therefore serve as indicative of trends rather than an accurate point estimate